Apparent viscosity of espada mango pulp - Oliveira, Relyson Gabriel Medeiros; Lopes, Carlos Cesar Bezerra; Melo, Joao Carlos Soares; Costa, Carlos Helaidio Chaves; Badaro, Adair Divino Silva (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
The rheological properties knowledge about food products is vital to the processes of equipment design and evaluation. The apparent viscosity of the pulps, for example, varies a lot during its processing, and it can preclude this processing with higher concentrations. Therefore, the objective of this work is to study the apparent viscosity behavior of espada mango pulp at temperatures of 15, 25, 35, 45 and 55° C and at concentrations of 20 and 16° Brix. The pulps apparent viscosity measurements were determined using an analog rotational viscometer, at different rotation speeds of the equipment (0,6; 1,5; 3,0; 6,0; 12; 30 and 60 rpm). All experiments were carried out in triplicate and, for calculation, it was used the average of the obtained values. The apparent viscosity of espada mango pulp tended to decrease with the increasing of rotation speed and temperature (in the studied concentrations). The espada mango pulp presented a behavior of a non-Newtonian fluid, of a pseudoplastic fluid. The equations adjusted to the experimental data of the espada mango pulp apparent viscosity can be used to estimate their apparent viscosity.